Heat Exchange from the Toucan Bill Reveals a Controllable Vascular Thermal Radiator - Tattersall, Glenn J.; Andrade, Denis V. [UNESP]; Abe, Augusto Shinya [UNESP] (Amer Assoc Advancement Science, 2009)
The toco toucan (Ramphastos toco), the largest member of the toucan family, possesses the largest beak relative to body size of all birds. This exaggerated feature has received various interpretations, from serving as a sexual ornament to being a refined adaptation for feeding. However, it is also a significant surface area for heat exchange. Here we show the remarkable capacity of the toco toucan to regulate heat distribution by modifying blood flow, using the bill as a transient thermal radiator. Our results indicate that the toucan's bill is, relative to its size, one of the largest thermal windows in the animal kingdom, rivaling elephants' ears in its ability to radiate body heat.